2020
DOI: 10.4314/ahs.v20i2.15
|View full text |Cite
|
Sign up to set email alerts
|

Condom use: a less travelled route among minibus taxi drivers and their taxi queens in KwaZulu-Natal, South Africa

Abstract: Background: Despite significant gains in the HIV epidemic in South Africa, with reduction in mortality and elimination of vertical transmission, national HIV prevalence remains high, with women rather than men continuing to bear higher bur- den of the disease. Population subgroups, through ignorance, disbelief or recklessness, continue to engage in risky sexual behaviour. A substantial proportion of minibus taxi drivers engage in risky sex, seldom seeing themselves at risk for STIs or HIV/AIDS. These taxi driv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
(25 reference statements)
4
1
0
Order By: Relevance
“…Furthermore, the implication of alcohol use in condomless sex as reported in previous studies [45,56,57] also resonates in the present study. Against this backdrop, the population of the present study could benefit from sexual health programs that embed socio-decision making and self-regulation skills, which have been found to be protective against risky sexual practices [58,59] as well as unhealthy drinking and condomless sex [60][61][62].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Furthermore, the implication of alcohol use in condomless sex as reported in previous studies [45,56,57] also resonates in the present study. Against this backdrop, the population of the present study could benefit from sexual health programs that embed socio-decision making and self-regulation skills, which have been found to be protective against risky sexual practices [58,59] as well as unhealthy drinking and condomless sex [60][61][62].…”
Section: Discussionsupporting
confidence: 91%
“…Sexual agency demonstrated by some female participants in negotiating condom use-in line with previous studies [44,45]-contradicts traditional stereotypes that portray East Asian and sub-Saharan African women as compliant and lacking power to negotiate condom use [11,46,47]. However, considering that some female participants may still feel less confident to access and negotiate condom use, it may be necessary for interventions to focus on improving sexual assertiveness and negotiation skills of international students to boost their confidence in accessing, negotiating and using condoms as low condom negotiation among women in particular increases likelihood of condomless sex [48].…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, the implication of alcohol use in condomless sex as reported in previous studies 45,56,57 also resonates in the present study. Against this backdrop, the population of the present study could bene t from sexual health programs that embed socio-decision making and self-regulation skills, which have been found to be protective against risky sexual practices 58, 59 as well as unhealthy drinking and condomless sex [60][61][62] .…”
Section: Discussionsupporting
confidence: 92%
“…Sexual agency demonstrated by some female participants in negotiating condom use-in line with previous studies 44,45 -contradicts traditional stereotypes that portray East Asian and sub-Saharan African women as compliant and lacking power to negotiate condom use 11,46,47 . However, considering that some female participants may still feel less con dent to access and negotiate condom use, it may be necessary for interventions to focus on improving sexual assertiveness and negotiation skills of international students to boost their con dence in accessing, negotiating and using condoms as low condom negotiation among women in particular increases likelihood of condomless sex 48 .…”
Section: Discussionsupporting
confidence: 70%
“…Although in this study we did not classify whether condomless sex was with a regular or casual partner, the decision not to use condoms could also be influenced by the type of sexual relationship a person is involved in [33][34][35][36]. Previous studies conducted in this rural setting found that low condom use at last sex was associated with having a regular sexual partner or an older partner [37,38].…”
Section: Discussionmentioning
confidence: 86%